Freak scenes American indie cinema and indie music cultures - Sexton, Jamie (Edinburgh University Press, 2023)
Freak Scenes explores the increased licensing of indie music and representation of indie music cultures within American independent cinema since the 1980s. Indie music has, since the 2000s, become highlighted in some indie films as an attraction, but this book probes how the appeal of indie music stretches back to the late 1970s, when punk music made its impact on filmmaking. Sexton looks at a range of issues where indie music and indie film intersect, including commercial concerns, the growth of niche marketing, the increased employment of popular music in cinema and questions of authenticity, as well as the fraught tensions between commercial and artistic concerns. Case studies include: sonic authorship and indie music, representations of punk and indie scenes on screen, and an exploration of how racial and gender issues inform the representation and reception of indie cultures on film
Title from publisher's bibliographic system (viewed on 19 Oct 2023)
Introduction A Brief History of Indie Music in American Indie Film Sonic Authorship 1: Gregg Araki Sonic Authorship 2: Sofia Coppola Documenting Scenes and Performers 1: Punk, Smithereens and Suburbia Documenting Scenes and Performers 2: Grunge and Riot Grrrl Indie Music, Film, and Race 1: Medicine for Melancholy and Pariah Indie Music, Film, and Race 2: Sorry to Bother You Conclusion NotesBibliography
Keywords: Independent films / United States / History and criticism; Motion pictures and rock music; Rock musicians in motion pictures